Sustainability & Circular Economy for electronic control units within the automotive industry - Abel, Oscar; Groth, Ola (My University, 2023)
The rapid evolution of the automotive industry, driven by advancements in technology and strict sustainability targets, demands the optimization of resources. Within this context, the exploration of remanufacturing, repair, and reuse strategies for electronic control units (ECUs) becomes critical. This thesis dives into the complex dynamics between OEMs and 1st-tier suppliers, focusing on the feasibility and implications of circular economy strategies in automotive electronics. The study investigates two key aspects: the feasibility of implementing circular strategies for ECUs and the potential challenges. For the former, the work explores the hardware, software, and quality requirements together with the OEMs' expectation of "as good as new or better.". For the latter, the research studies the future implications of implementing circular strategies such as remanufacturing, repair, or reuse. Drawing on empirical data and the application of a robust analytical framework, this thesis provides key insights and strategic recommendations. Cybersecurity and hardware quality were identified as pivotal areas demanding innovative solutions. Further, it emphasizes the need for realistic expectations from OEMs, advocating for a necessary shift in the definition of "as good as new" within the circular economy framework for electronics. The study highlights the increasing feasibility of circular strategies due to regulatory changes, innovation, and the transition to centralized hardware and software architectures. The research offers critical contributions to the academic and practical discussion on automotive electronics sustainability. It introduces a new perspective on circular economy strategies, highlighting the importance of defining requirements, fostering compromise, and promoting innovation within a complex inter-organizational context. The recommendations presented in this work are intended to inform strategic decision-making for OEMs and first-tier suppliers, guiding them toward a more sustainable and efficient future. Finally, this thesis provides a comprehensive roadmap for OEMs and suppliers for their sustainability journey, showing potential opportunities for future exploration. While not providing a full roadmap for the many issues confronting the automotive industry, it delivers essential insights into the field's current state and future directions. By doing so, it seeks to support further research and practical initiatives in automotive electronics remanufacturing, repair, and reuse, ultimately contributing to the realization of a sustainable automotive industry.
Keywords: current trends, challenges, opportunities, reuse, remanufacturing, repair, electronics, ECU, automotive, vehicle, sustainability, circular